Aortic Valve Replacement for Patients with Severe Aortic Stenosis and Severe Left Ventricular Dysfunction - Mortality Risk Factors - Bakkali, Abderrahmane; Koulekey, Dodji; Sayah, Rochde; Jaabari, Imad; Ait Houssa, Mahdi; Laaroussi, Mohamed (Integrative Journal of Medical Sciences, 2017)
Severe left ventricular dysfunction increases the surgical risk of aortic valve replacement on aortic valvular stenosis. Several risk factors of hospital mortality have been reported in heterogeneous series. The aim of this study was to identify mortality risk factors of aortic valve replacement in patients with severe aortic stenosis and severe left ventricular dysfunction. To avoid biases of associated diseases, our study has been focused on isolated aortic stenosis. 46 patients, with AS and severe left ventricular dysfunction who underwent AVR, were enrolled in this retrospective study. The mean age was 59 ± 12.70 years. 69.6% of patients were in class III or IV NYHA. The mean left ventricular ejection fraction (LVEF) was 32.3 ± 5.3%, and the mean EuroSCORE was 12.20 ± 8.70. The hospital mortality was 15.20%. The morbidity was marked mainly by low output syndrome in 30.4% of cases. Logistic regression in univariate analysis reveals functional class, renal failure, congestive heart failure, and LVEF as factors related to the risk of hospital mortality. Multivariate logistic regression analysis found renal failure (OR = 11.94, CI [2.65 -72.22], p = 0.03) and congestive heart failure (OR = 25.33, CI [3 43 -194.74], p = 0.009) as independents risk of hospital mortality. The mean follow-up was 59.6 ± 21 months. Late mortality was 5%. Congestive heart failure and preoperative renal failure are the main independent hospital mortality risk factors of aortic valve replacement in patients with severe aortic stenosis and severe left ventricular dysfunction. Late mortality might be inversely related to LV recovery.